2008
DOI: 10.1080/01902140801935082
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Nigella Sativa on Lung Injury of Sulfur Mustard–exposed Guinea Pigs

Abstract: The lung is one of the most exposable organs to chemical warfare agents such as sulfur mustard (SM) gas. Airway hyperresponsiveness and lung inflammation are reported in chemical warfare victims. There is no definite treatment for respiratory disorders induced by SM exposure. However, the protective effect of Nigella sativa on inflammatory process was shown. In the present study, the protective effect of Nigella sativa on tracheal responsiveness and lung inflammation of SM exposed guinea pigs was examined. Gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…TR to methacholine, total white blood cell count of lung lavage, and differential white blood cell were done 14 d post exposure. The results showed a preventive effect of N. sativa on TR of sulfur mustard gasexposed guinea pigs [99] . The possible beneficial effects of the seeds of N. sativa L. on experimental lung injury in male Wistar rats after pulmonary aspiration of different materials was investigated.…”
Section: +mentioning
confidence: 78%
“…TR to methacholine, total white blood cell count of lung lavage, and differential white blood cell were done 14 d post exposure. The results showed a preventive effect of N. sativa on TR of sulfur mustard gasexposed guinea pigs [99] . The possible beneficial effects of the seeds of N. sativa L. on experimental lung injury in male Wistar rats after pulmonary aspiration of different materials was investigated.…”
Section: +mentioning
confidence: 78%
“…It has been shown that pretreatment with hydroethanolic extract of N. sativa in guinea pigs with COPD induced by cigarette smoking was as effective as vitamin C in reducing inflammation and tracheal responsiveness (Keyhanmanesh, Nazemiyeh, et al, 2014). Moreover, the protective and antioxidant effects of aqueous extract of N. sativa seeds in sulphur mustard-exposed chemical war victims (Boskabady & Farhadi, 2008) and the effects of N. sativa hydroethanolic extract in sulphur mustard-exposed guinea pigs have been shown (Hossein et al, 2008).…”
Section: Antioxidant Activitymentioning
confidence: 97%
“…Hydroethanolic extract of N. sativa treatment in ovalbumin sensitized guinea pigs could improve total white blood cell (WBC) and eosinophil counts in the lung lavage (Boskabady, Keyhanmanesh, Khamneh, & Ebrahimi, 2011). The protective effect of N. sativa on lung inflammation of sulphur mustard-exposed guinea pigs showed the ameliorating and preventive effects on total WBC and eosinophils which can be related to anti-inflammatory and antioxidant properties of the plant (Hossein, Nasim, & Sediqa, 2008).…”
Section: Anti-inflammatory Activitymentioning
confidence: 97%
See 1 more Smart Citation
“…In vivo small animal models provide preliminary evaluation of drug treatment effectiveness [17,18], but there can be inherent issues with these models. Owing to their small body size and variations in physiology, small animals are not always the best models to extrapolate to man in the evaluation of lung injury.…”
Section: The Modelmentioning
confidence: 99%